2023
DOI: 10.1021/acs.biomac.2c01262
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Calcium Phosphate Deposition on Collagen-Inspired Short Peptide Nanofibers for Application in Bone Tissue Engineering

Abstract: In recent years, immense attention has been devoted over the production of osteoinductive materials. To this direction, collagen has a dominant role in developing hard tissues and plays a crucial role in the biomineralization of these tissues. Here, we demonstrated for the first time the potential of the shortest molecular pentapeptide domain inspired from collagen toward mineralizing hydroxyapatite on peptide fibers to develop bone-filling material. Our simplistic approach adapted the easy and facile route of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…2D cell culture study was carried out to measure cellular growth and proliferation on composite hydrogels . The detail study of 2D cell culture was reported earlier in our previous studies. ,, In this study, different time points of 48, 72, and 120 h have been selected to check the biocompatibility of the composite scaffolds toward neuroblastoma cells. Then, the adhered cells on the composite scaffolds were stained by FDA (fluorescein diacetate) and PI (propidium iodide) to evaluate live and dead cells, respectively. , Then cells were observed at 10× magnification through CLSM (Zeiss Confocal Microscope, LSM880, Carl Zeiss).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…2D cell culture study was carried out to measure cellular growth and proliferation on composite hydrogels . The detail study of 2D cell culture was reported earlier in our previous studies. ,, In this study, different time points of 48, 72, and 120 h have been selected to check the biocompatibility of the composite scaffolds toward neuroblastoma cells. Then, the adhered cells on the composite scaffolds were stained by FDA (fluorescein diacetate) and PI (propidium iodide) to evaluate live and dead cells, respectively. , Then cells were observed at 10× magnification through CLSM (Zeiss Confocal Microscope, LSM880, Carl Zeiss).…”
Section: Methodsmentioning
confidence: 99%
“…Alamar Blue, a specific fluorescence indicating dye, is used to assess cellular proliferation on the composite hydrogel in different time periods. , The detail study is reported in our earlier literatures. ,, Cellular proliferation was carried out at different intervals of 48, 72, and 120 h. In particular, triplicate studies of this experiment were done to get the averaged data which can be represented as mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations